Sustainable Food Systems in Fruits and Vegetables Food Supply Chains - Cassani, Lucía; Gomez-Zavaglia, Andrea (Frontiers in Nutrition, 2022)
Fruits and vegetables wastes (e.g., peel fractions, pulps, pomace, seeds) represent ~16% of total food waste and contribute ~6% to global greenhouse gas emissions. The diversity of the fruit-horticultural production in several developing countries and the excess of certain fruits or vegetables in the months of greatest production offer unique opportunities for adding value to these wastes (co-products). Within the scope of the Circular Economy, valorization of such wastes for the production of innovative bio-ingredients can open great market opportunities if efficiently exploited. In this context, this review deals with the current situation of wastes arising from fruits and vegetables (availability, characterization) as sources of valuable ingredients (fiber, polyphenols, pigments) suitable to be incorporated into food, pharmaceutical and cosmeceutical products. In addition, an integral and systematic approach including the sustainable technologies generally used at both lab and industrial scale for efficient extraction of bioactive compounds from fruits and vegetables wastes are addressed. Overall, this review provides a general updated overview regarding the situation of fruits and vegetables chain supplies in the postpandemic era, offering an integrative perspective that goes beyond the recovery of fiber and phytochemicals from the previous mentioned wastes and focuses on whole processes and in their social and economic impacts.